Расчет надежности технологического процесса по одному показателю качества продукции - Божко, В. П.; Каширина, О. В. (НТУ "ХПИ", 2004)
The reliability is one of the main properties of technical objections, then the creation of technological process has high requirement for reliability’s property. The preliminary calculation of reliability allowed determining "dangerous" places of technological process and would develop arrangements for eliminations of the refusal’s bottom
Keywords: изделия авиационной промышленности; безотказное функционирование; поток отказов; насос-регулятора НР3; цилиндрические поверхности шестерни